Cardiorespiratory fitness and electroanatomical remodelling in patients with atrial fibrillation. (11th May 2021) - Mishima, RS; Elliott, AD; Ariyaratnam, JP; Jones, D; Nguyen, O; Martin, L; Noubiap, JJ; Malik, V; Mahajan, R; Lau, DH; Sanders, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Atrial fibrillation (AF) is the most common clinically-relevant arrhythmia. Its initiation and maintenance is linked to the presence cardiovascular risk factors such as hypertension and obesity. Higher cardiorespiratory fitness (CRF) has been associated with a better prognosis. However, specific electroanatomical features associated with baseline CRF have not been described.  Purpose: Compare electroanatomical substrate across exercise capacity levels in patients with AF Methods: Patients referred for de novo AF radiofrequency ablation at the Centre for Heart Rhythm Disorders from August 2017 until June 2020 were screened for inclusion and CRF was evaluated in metabolic equivalents (METs) by a symptom-limited maximal treadmill exercise test using the standard Bruce protocol prior to ablation. Predicted CRF was calculated based on established equations and patients were categorized according to the percentage of predicted CRF achieved; low (<85%), adequate (85-100%) and high (>100%). Total mean and regional peak-to-peak bipolar voltages, percent of low voltage areas (% LVA), conduction velocity (CV) and percent of complex fractionated electrograms (% CFE) in sinus rhythm were compared across groups.  Results: There were no between-group differences in baseline characteristics, medication use or echocardiographic features. Total mean voltage was significantly lower in the low CRF group compared to both adequate and high CRF. Compared to the high CRF group, roof (3.25 ± 1.2 mV vs 1.9 ± 1.3 mV, p < 0.05), posterior (3.8 ± 1.8 mV vs 1.7 ± 0.9 mV, p < 0.001) and inferior mean voltages (3.4 ± 2 mV vs 1.6 ± 0.7 mV, p < 0.05) were significantly lower in the low CRF group (figure 1A). Furthermore, compared with the adequate CRF group, mean voltages were significantly lower in the posterior (3.7 ± 1.5 mV vs 1.7 ± 0.9 mV, p < 0.001), inferior (3.4 ± 1 mV vs 1.6 ± 0.7 mV, p < 0.001) and lateral (4.2 ± 2.2 mV vs 2.1 ± 1.4 mV, p < 0.05) walls of the low CRF group. Anterior and septal mean voltages were not significantly different across CRF groups (P for trend = 0.07, 0.3 and 0.15, respectively). Conduction velocities were not significantly different across groups. The inferior %LVA was significantly higher in the low CRF (5.6 ± 6%) compared to adequate CRF group (23 ± 18%) (p < 0.05) (figure 1B). Total and regional % CFE was higher in the low CRF compared to adequate and high CRF. Conclusion: Participants in the lower baseline CRF category showed significant reductions in regional voltages along with higher fractionation with preserved conduction velocities. Research on the effect of physical activity and CRF on left atrial arrhythmogenic substrate is required.